(untitled) (American Journal of Islam and Society, 2003)
This is an appealing and clearly written account of how European thinkers from late medieval to early modern times reflected upon and explored the question of what to do about people of different religions and cultures. In other words, how should their divergent opinions be understood and, eventually, what practical dispositions should be taken toward them? Cary Nederman devotes the introduction and first chapter to an excellent, detailed explanation of the book’s focus and goals. Simply put, he is intent upon challenging two currently dominant views: that toleration emerged in Europe only at the time of the Reformation, and that it is ineluctably linked with the kind of political liberalism usually associated with John Locke. To this end, he calls the reader’s attention to expressions of religious, and even somewhat political, toleration that appear early in the twelfth century and continue well into the sixteenth century. Unfortunately, he does not succeed in this ambitious, even appealing, stratagem as fully as he would have wished, for he admits in passing that he is content to “offer illustrations,” instead of a “comprehensive account,” of this phenomenon ...